2023
DOI: 10.1073/pnas.2221313120
|View full text |Cite
|
Sign up to set email alerts
|

The nitrate transporter NRT2.1 directly antagonizes PIN7-mediated auxin transport for root growth adaptation

Abstract: As a crucial nitrogen source, nitrate (NO 3 − ) is a key nutrient for plants. Accordingly, root systems adapt to maximize NO 3 − availability, a developmental regulation also involving the phytohormone auxin. Nonetheless, the molecular mechanisms underlying this regulation remain poorly understood. Here, we identify low-nitrate-resistant mutant ( lonr ) in Arabidopsis ( Arabidopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…A series of assays confirmed the ability of PIN7 and NRT2.1 to physically interact with one another when NO 3 - levels are low, thereby suppressing the PIN7-mediated acropetal efflux of auxin, thus slowing the elongation of primary roots. Together these results support a model in which NRT2.1 is capable of influencing root growth activity through interactions with the PIN7-mediated auxin transport machinery when levels of available NO 3 - are low ( Wang et al., 2023 ).…”
Section: Plant Growth and Developmentsupporting
confidence: 74%
“…A series of assays confirmed the ability of PIN7 and NRT2.1 to physically interact with one another when NO 3 - levels are low, thereby suppressing the PIN7-mediated acropetal efflux of auxin, thus slowing the elongation of primary roots. Together these results support a model in which NRT2.1 is capable of influencing root growth activity through interactions with the PIN7-mediated auxin transport machinery when levels of available NO 3 - are low ( Wang et al., 2023 ).…”
Section: Plant Growth and Developmentsupporting
confidence: 74%
“…In this study, LBS6-treated plants showed higher expression of SYM29 , explaining the plausible reason behind the better growth in LBS6-treated plants under optimum N and N-deficient conditions. Additionally, the nitrate level in the root regulates auxin transport activity by differentially regulating the expression of NRT2.1 and thus plant growth ( Wang et al., 2023 ). Nitrate is reduced to nitrite in the cytosol by nitrate reductase, which is then transported to the chloroplast and converted to ammonia by nitrite reductase (NiR) ( Orsel et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the nitrate level in the root regulates auxin transport activity by differentially regulating the expression of NRT2.1 and thus plant growth (Wang et al, 2023). Nitrate is…”
Section: Discussionmentioning
confidence: 99%
“…NRT2.1, in contrast to NPF6.3/NRT1.1, is a unidirectional nitrate transporter, which is not required for nitrate‐induced calcium influx, and is not required for nitrate‐dependent alleviation of proton toxicity (Fang et al ., 2016). Recently, progress has been made on how NRT2.1 exerts its effects on nitrate regulation of root growth, with a direct interaction between NRT2.1 and the auxin transporter PIN7 serving to inhibit PIN7‐mediated auxin efflux, depending on nitrate availability (Wang et al ., 2023).…”
Section: Nitrogen Uptake and Regulationmentioning
confidence: 99%